Regional intra-arterial vs. systemic chemotherapy for the treatment of advanced pancreatic cancer: a systematic review and meta-analysis - Cao, Yanjie; Yu, Dedong; Wu, Yun; Zhu, Wei (Frontiers in Oncology, 2024)
Regional intra-arterial chemotherapy (RIAC) has been clinically used as a new chemotherapy regimen for the treatment of advanced pancreatic cancer. However, its efficacy remains controversial. Herein, we performed a systematic review and meta-analysis to investigate the efficacy and safety of RIAC versus systemic chemotherapy for advanced pancreatic cancer. PubMed, Embase, Web of Science, and the Cochrane Library were searched to access studies comparing the safety and efficacy of RIAC with systemic chemotherapy. Two researchers independently completed data extraction and quality assessment, and STATA16 was used for statistical analyses. The Odds ratios (OR) or risk difference (RD) and 95% confidence intervals (CI) were computed from the data from included studies. Eleven eligible studies were included in the quantitative analysis, and 627 patients were included in our meta-analysis. Patients treated with RIAC had significantly better partial remission (PR)(OR = 2.23, 95% CI: 1.57, 3.15, I2 = 0%) and lower complication rate (OR = 0.45, 95% CI: 0.33, 0.63, I2 = 0%) than patients treated with systemic chemotherapy. The median survival times were longer in patients receiving RIAC than those receiving systemic chemotherapy. Compared with systemic chemotherapy, RIAC had a higher PR, greater clinical benefit, and fewer complications when treating advanced pancreatic cancer.